アルツハイマー病疾患修飾薬開発の潮流 - 木村, 禎治 (日本薬理学会年会要旨集, 2023)
In the early 1990s, the amyloid cascade hypothesis was proposed based on genetic research into familial Alzheimer's disease (AD) as the mechanism of AD onset and progression. Subsequently, numerous clinical trials of agents based on this hypothesis were conducted, leading to many failures. However, these research results contributed to 1) the identification of toxic species, 2) the selection of the appropriate subject population, 3) the logical determination of dosages and administration durations based on biomarkers, and 4) the development of highly sensitive primary endpoints. This presentation provides an overview of the history of anti-Aβ drug development, non-clinical research on mechanisms of action, and clinical trial results, including biomarkers. It also outlines the prospects for future Alzheimer's disease drug development.